A further study on the wolf spider subfamily Artoriinae from China (Araneae: Lycosidae) - Wang, Lu-Yu; Framenau, Volker W.; Zhang, Zhi-Sheng (Zootaxa, 2021)
The further collection and study of Chinese wolf spiders, family Lycosidae Sundevall, 1833, expand the known distribution of the subfamily Artoriinae Framenau, 2007 from Yunnan to Guangxi, Guizhou, and Sichuan Provinces of South China. Sinartoria gen. nov. is described to include two new species, S. damingshanensis sp. nov. (type species) and S. zhuangius sp. nov. In addition, a new Artoria species, A. hamata sp. nov. is described and new distribution records for A. ligulacea (Qu, Peng & Yin, 2009) and A. parvula Thorell, 1877 are provided. Within the Artoriinae, Sinartoria gen. nov. appears to be most similar to the South American Lobizon Piacentini & Grismado, 2009, but their relationship will remain contentious without a comprehensive phylogenetic analysis of artoriine genera.